7+6(6z+7)=-2(-4z-2)+2

Simple and best practice solution for 7+6(6z+7)=-2(-4z-2)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+6(6z+7)=-2(-4z-2)+2 equation:


Simplifying
7 + 6(6z + 7) = -2(-4z + -2) + 2

Reorder the terms:
7 + 6(7 + 6z) = -2(-4z + -2) + 2
7 + (7 * 6 + 6z * 6) = -2(-4z + -2) + 2
7 + (42 + 36z) = -2(-4z + -2) + 2

Combine like terms: 7 + 42 = 49
49 + 36z = -2(-4z + -2) + 2

Reorder the terms:
49 + 36z = -2(-2 + -4z) + 2
49 + 36z = (-2 * -2 + -4z * -2) + 2
49 + 36z = (4 + 8z) + 2

Reorder the terms:
49 + 36z = 4 + 2 + 8z

Combine like terms: 4 + 2 = 6
49 + 36z = 6 + 8z

Solving
49 + 36z = 6 + 8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8z' to each side of the equation.
49 + 36z + -8z = 6 + 8z + -8z

Combine like terms: 36z + -8z = 28z
49 + 28z = 6 + 8z + -8z

Combine like terms: 8z + -8z = 0
49 + 28z = 6 + 0
49 + 28z = 6

Add '-49' to each side of the equation.
49 + -49 + 28z = 6 + -49

Combine like terms: 49 + -49 = 0
0 + 28z = 6 + -49
28z = 6 + -49

Combine like terms: 6 + -49 = -43
28z = -43

Divide each side by '28'.
z = -1.535714286

Simplifying
z = -1.535714286

See similar equations:

| 2+3=4-6 | | x-x(.33)=284.75 | | 3x+3+x=7 | | 3(4x-3)=3+2(5x-3) | | 1a-30=2a+6 | | x+3=2.8 | | x-.33=284.75 | | 2-5(-6y-2)=-2(-4y-3)-3 | | 10+-3x+3x=10 | | 10+-3y+3y=10 | | -31+p=8(-8-4p) | | 4-2y=9+2y | | 5n+6-6n=-4 | | 10x+18y=-11 | | -5p-34=-4 | | 230=150+0.2s | | 12v+23=12v+16 | | .25x-5=8 | | 5x+31=6 | | .23x-5=8 | | 5x(5-9)=35 | | 16x+4+110=3x+11 | | 6+2(3j-3)=4(1+j) | | 2a^2-3a-14=0 | | x/(x-3)+x/2=6x/(2x-6) | | 6x-3y=2 | | 7x-4=6x+5 | | 1x-1+5x=23 | | 3(6+5y)=2(-5+46) | | x-x(.6)=54 | | -4(4t^2-289)=0 | | 20t=60-40t |

Equations solver categories